Намисто з Чорнівського городища ХІІІ ст. (дослідження 1999-2020 рр.) - Калініченко, Віталій; Пивоваров, Сергій (Київ, Інститут археології НАН України, 2022)
Під час археологічних робіт на Чорнівському городищі виявлено різноманітні прикраси, якими оздоблювався повсякденний і святковий одяг представниць жіночої статі, які мешкали на території феодального замку в першій половині - середині ХІІІ ст. Матеріал з якого вони зроблені, типологія та технологія виробництва дозволяють говорити, що конкретні прикраси могли належати різним соціальним, етнічним і віковим групам місцевих жительок. Під час дослідження городища виявлено 72 екземпляри цілих і фрагментованих намистин. Вони представлені: виробами з металу - еліпсоподібними намистинами прикрашеними філігранню й зерню, ажурними каркасними намистинами оздобленими зерню, фігурною намистиною; мушлями каурі; скляними виробами - монохромними, поліхромними та із металевою фольгою намистинами. During the archeological works on the Chornivka hill-fort various ornaments which decorated the everyday and festive clothes of women having lived on the territory of the feudal castle in the first half - the mid-13-th century were discovered. The material from which they are made, typology and production technology suggest that definite jewelry could belong to different social, ethnic and age groups of local people. The old Ukrainian women’s necklaces and breast adornment in addition to aesthetic function also had protective and social ones. These categories include a number of necklaces with numerous pendants. Their form and ornamentation reflected the local population worldviews, where together with Christian symbols, pagan elements were used. All of this shows the combination in these ornaments the primitive and Christian principles and the syncretism of their semantic content. One of the most numerous groups of women’s breast ornaments from the hill-fort is a necklace. Most of the beads are represented by single finds but their clusters (minithesaurus) have also been recorded. During the study of the hill-fort 72 whole and fragmented beads were found. They are represented by metal items such as elliptical beads decorated with filigree and grain, openwork frame beads decorated with grain, figured beads; cowrie shells; glass items - monochrome, polychrome and beads with metal foil. The beads found on the hill-fort significantly increase the information on the elements of old Ukrainian women’s costume decoration in the region and allow tracing the trade, economic, cultural and possibly military and political ties of the feudal castle in the first half - the mid-13-th century.
Necklace from Chornivka hill-fort of the 13th century (excavation of 1999-2020)
Keywords: Буковина; Чорнівське городище; намисто; металеві й скляні намистини; мушлі каурі; зернь; філігрань; середньовіччя; археологічні дослідження